Peran Steroid pada Pneumocystis Pneumonia Ditinjau Berdasarkan Imunopatogenesis : [Immunopathogenesis of Steroid in Pneumocystis Pneumonia] - Resti Yudhawati; Whendy Wijaksono (Faculty of Medicine Universitas Airlangga, 2019)
Pneumocystis Pneumonia (PCP) is a potentially life-threatening infection that can occur in individuals who are immunocompromised. In PCP steroid use is still recommended especially in patients with moderate and severe severity. Corticosteroids are given along with anti-pneumocystis therapy and are known to reduce the incidence of mortality and respiratory failure associated with PCP. Innate immunity and adaptive immunity are symbiotic relationships to provide optimal defense for the lungs and other organs and tissues from infection PCP. The corticosteroid mechanism in PCP is based on an anti-inflammatory mechanism especially its role in inhibiting neutrophils. Many clinicians believe the administration of anti-pneumocystis causes the acceleration of inflammation. Because the inflammatory process increases when anti-pneumocystis therapy is started, corticosteroid therapy is useful before inflammation occurs which causes extensive damage to the lungs.